Analisi di costo di pemetrexed vs docetaxel nel trattamento di seconda linea del carcinoma polmonare non a piccole cellule - Ravasio, Roberto (Farmeconomia. Health Economics and Therapeutic Pathways, 2005)
OBJECTIVES: to compare costs of pemetrexed versus docetaxel in patients with non-small cell lung cancer previously treated with chemotherapy paying special attention to the adverse events. MATERIALS AND METHODS: a cost analysis was carried out performing comparison between pemetrexed and docetaxel. Clinical data (overall survival) and resource consumption (chemotherapy drugs, G-CSF, and hospitalizations due to adverse events) were obtained from a randomized phase III trial. The economic evaluation was based on direct costs using local Italian unit costs (euro 2005). The perspective was the National Health Service’s. RESULTS: the study results showed that mean survival of pemetrexed (8,3 months; 0,69 years) was higher than mean survival of docetaxel (7,9 months; 0,66 years). The mean cost of treatment with pemetrexed was 8.684,26 euros and with docetaxel was 6.182,87 euros. This difference was nearly offset by the difference in the costs of adverse events: the mean cost of adverse events due to chemotherapy treatment with pemetrexed (493,93 euros) turned out to be lower than with docetaxel (2.394,34 euros). CONCLUSION: the present cost-analysis could be a stable ground for a further cost-utility analysis, aimed at reaching a more cost-effectiveness management of the chemotherapy-related adverse effects in patients with NSCLC.